2021
DOI: 10.1038/s41598-021-93156-1
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin protects against sepsis capillary leak syndrome by activating endothelial α1AMPK

Abstract: Sepsis capillary leak syndrome (SCLS) is an independent prognostic factor for poor sepsis outcome. We previously demonstrated that α1AMP-activated protein kinase (α1AMPK) prevents sepsis-induced vascular hyperpermeability by mechanisms involving VE-cadherin (VE-Cad) stabilization and activation of p38 mitogen activated protein kinase/heat shock protein of 27 kDa (p38MAPK/HSP27) pathway. Canagliflozin, a sodium-glucose co-transporter 2 inhibitor, has recently been proven to activate AMPK in endothelial cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…improving intestinal barrier function have also been demonstrated in animal models (30,31). The beneficial effects of SGLT2 inhibitors were observed across all categories of ICU admission but were most evident in reducing nonoperative ICU admissions, which in our cohort referred to emergency admissions due to nonsurgical causes.…”
Section: Discussionsupporting
confidence: 57%
“…improving intestinal barrier function have also been demonstrated in animal models (30,31). The beneficial effects of SGLT2 inhibitors were observed across all categories of ICU admission but were most evident in reducing nonoperative ICU admissions, which in our cohort referred to emergency admissions due to nonsurgical causes.…”
Section: Discussionsupporting
confidence: 57%
“…This class of drug may exert "off-target" cardiovascular benefits by modulating vascular endothelial cell activation and alleviating endothelial cell dysfunction. This is also supported by the work of Ange et al, who recently showed that CANA activates the alpha-1 AMPK-dependent pathway in human endothelial cells exposed to human septic plasma [32]. Furthermore, Behnammanesh et al have demonstrated that CANA stimulates the expression of heme-oxygenase (HO)-1, a highly inducible antioxidant, in vascular smooth muscle cells.…”
Section: Mechanisms Underlying Protective Effects Of Cana Against Iri In Vasculaturementioning
confidence: 67%
“… Acting on the α1AMPK-dependent pathway. [ 152 ] Abbreviations : SGLT2, sodium-glucose cotransporter-2; LPS, lipopolysaccharides; UCP2, uncoupling protein 2; CLP, cecal ligation and puncture; AMPK, adenosine monophosphate-activated protein kinase. …”
Section: Introductionmentioning
confidence: 99%